Pathogenic gut microbiota associated with striped catfish, Pangasianodon hypophthalmus cultured in Bangladesh and their antibiotic sensitivity pattern (Dhaka University Journal of Biological Sciences, 2020)
To identify the gut bacteria of Pangasianodon hypophthalmus (striped catfish; Pangas) using classical and molecular approach was carried out. Total bacterial count (TBC) in the gut of pangas from farm and market samples were found 5.07 ± 1.70 × 106 and 1.40 ± 0.47 × 106 cfu/g, respectively. The gut microbiota of pangas was dominated by members of the Gram-negative genera. Only three isolates (MyF1/1, MyF1/4 and GaW1/2) were found to be Gram-positive among the 16 representative isolates. Using 16S rRNA gene sequencing; Bacillus, Macrococcus, Citrobacter, Aeromonas, Proteus, Klebsiella, Enterobacter, Escherichia and Edwardsiella were found to be associated with the gut of this fish. Among them, Aeromonas was the most dominant genus (5 out of 16). Antibiotic sensitivity pattern reflected that all the isolates were sensitive to gentamycin. Multiple antibiotics resistant isolates were also identified of which MyF3/13 (identified as Citrobacter amalonaticus) was found resistant against seven tested antibiotics. The presence of pathogenic bacteria in fish gut revealed the improper handling practices in fish market and unhygienic condition in the culture sites which might be a reason of fish-borne disease outbreaks. On the other hand, widespread use of various antibiotics in aquaculture without proper awareness may lead to resistance to multiple antibiotics.Dhaka Univ. J. Biol. Sci. 29(1): 61-73, 2020 (January)